REKRUTMEN CALON ANGGOTA LEGISLATIF PARTAI AMANAT NASIONAL PROVINSI RIAU PERIODE 2014-2019 - Allan Yanika; Tinov M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research describe about the recruitment politics of House of Representatives from National Amanat Party of Riau periode 2014-2019. Recruitment politics are function of political party that have purpose to keep acisstance of National Amanat Party of Riau.The methods of this research are cualitative descriptive methods that as a process analize the problem research with describe the subject and object research based on the empirical fact. The location of this research in DPW PAN Riau Province and researcher collect data from the books, goverment rules, journal, mass media, website and also deep interview with informan research such as head of PAN Riau, vice of KPPW DPW PAN Riau, functionarist PAN, and society.The conclution of this research are recruitment politics for House of Representatives from National Amanat Party held with open recruitment for all citizens The recruitment in National Amanat Party held by Teritory Election for win Comitee National Amanat Party of Riau. The process recruitment held based on AD/ART and rules of organization of National Amanat Party and also formality and informality factors.Keyword: recruitment, house of representative and political party.